Saint Vincent and the Grenadines. Significant achievements 2010 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Saint Vincent and the Grenadines during 2010 are identified, with respect to the needs and interests of the country, strengthening issues such as export, quarantine, trade, health, research, agribusiness, agrotourism, leadership, production , composting, seedlings, training, surveillance, animal health, standards, control of diseases and heteropterous pests, inclusion of young people, sweet potato and vegetable production, and attention to emergencies, such as Hurricane Tomás.